Trends in the utilisation of maternal and child healthcare services from the public and private health sectors in India, 2005–2021: an analysis of cross-sectional survey data - Niranjan Saggurti; Rajib Acharya; Abhishek Kumar; Anchal Purbey; Arupendra Mozumdar; Punit Mishra (BMJ Open)
Objectives To estimate the levels and trends of maternal and child healthcare (MCH) service utilisation in India across subsidised and unsubsidised health sectors and to explore total market approach to identify geographies where the private sector has potential to improve MCH services in India.Design and setting This study used three recent rounds of the National Family Health Survey (NFHS), a cross-sectional survey in India, conducted in 2005–2006, 2015–2016 and 2019–2021. Bivariate analysis and multinomial logistic regression were used to estimate the utilisation of key MCH indicators from subsidised and unsubsidised health sectors. Market sustainability of key MCH indicators was assessed by level of MCH services and subsidisation.Participants 36 850, 190 898 and 176 843 ever-married women aged 15–49 years, 4440, 22 500 and 15 334 children under 5 years of age with diarrhoea before the survey, and 2552, 6960 and 6117 children with symptoms of acute respiratory infections (ARI) in NFHS 2005–2006, 2015–2016 and 2019–2021, respectively.Outcome measures The study used three maternal healthcare indicators: women had four or more antenatal care (ANC) visits, had institutional delivery, and received postnatal care (PNC); and two child healthcare indicators: care seeking for ARI and diarrhoea.Results In India, utilisation of maternal healthcare services increased over the last 15 years: four or more ANC visits increased from 37% to 58% and PNC of mothers increased from 33% to 78% between 2005–2006 and 2019–2021. The results of the multivariate analysis showed that utilisation of ANC (67% from public vs 18% from private health facilities), institutional delivery (64% from public vs 25% from private health facilities) and PNC (73% from public vs 27% from private health facilities) was significantly higher (p<0.001) in public than in private health facilities. Care seeking for ARI and diarrhoea among children was significantly higher (p<0.001) in private than in public health facilities; care for ARI was 68% in private health facilities compared with 32% in public health facilities.Conclusions A targeted approach is needed to enhance the competitiveness of private sectors, especially in maternity care markets, to ensure the sustainability of healthcare services in India. Strengthening both the private and public sectors is crucial, with a focus on improving care quality and addressing regional disparities in access to maternal and child health services.